The profile of the academic production on men's artistic gymnastics from the web of science and scopus - Vargas, P. I.; Mendes Capraro, A. (Science of Gymnastics Journal, 2020)
The objective of this study was to describe the scientific production on men`s artistic gymnastics (MAG) in journals indexed on the Scopus and Web of Science platforms. To this end, we searched on both platforms for the keywords "men`s artistic gymnastics" and "male artistic gymnastics", with a non-specified date range. After applying the exclusion criteria, 52 scientific articles were found, distributed between 1994 and 2019. The year with the highest number of publications so far is 2018, with emphasis on the period between 2014 and 2018. The authors who contributed the most were Maurice Yeadon and Michael Hiley (both from British universities), Marco Bortoleto (from Brazil), and Ivan Cuk (from Slovenia). There is a predominance of MAG-related articles in the Science of Gymnastics Journal (21%), followed by the Journal of Biomechanics (7%). The articles deal with the biomechanics of gymnastics (34%), the rules of the sport and its judging (19%), the social, historical and political aspects of gymnastics (14%), morphological characteristics of athletes (10%), athletes` health (10%), gymnastics training aspects (8%), and finally, analyses of athletes` age over the years (6%).